Using Inductive Consciousness Raising Tasks to Teach Grammar at the College - Veni Roza (Proceedings of ISELT FBS Universitas Negeri Padang, 2014)
Teaching grammar at colleges in Indonesia has run quite long. The approach to grammar instruction that is common seen is teacher-centered or the teacher-led one. Teachers talk much to present the knowledge or to explain the material while learners receive the information. Such way of teaching grammar is tiring for teachers and boring for learners. They have to spend most of lesson time presenting and explaining grammatical knowledge, at the expense of little time for learners to use English. Using inductive consciousness-raising task is a good problem solving to relieve teachers form the burden of talking, enhance learners talk, create motivating learning environment and improve explicit knowledge retention. Because the tasks require learners to be actively engaged in the meaning-making process by interacting with their partners most of the time to work out the grammatical rule and the teacher just interferes when help is needed. This paper will talk about the use of inductive consciousness-raising tasks in teaching grammar on two topics with expectation to promote learners’ grammatical knowledge.